2020
DOI: 10.5812/archcid.102848
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iranian Nurses’ Knowledge and Anxiety Toward COVID-19 During the Current Outbreak in Iran

Abstract: Background:The world is affected by the Corona Virus Disease 2019 . Because of their direct contact with patients, health workers, especially nurses, play critical roles in the prevention of the COVID-19 outbreak through proper care and preventive procedures.Objectives: This study aimed to measure the awareness level of nurses in Shiraz, Iran, during the current COVID-19 outbreak. Methods: A self-administered questionnaire containing knowledge questions was distributed to 85 participants to complete. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

65
365
22
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(463 citation statements)
references
References 13 publications
65
365
22
11
Order By: Relevance
“…In this study, 74% ( with CI; 70 to 78.1) of the participants had good knowledge regarding the COVID-19 outbreaks. This is higher than with the study conducted in Iran [14,17] and Saudi Arabia [18]. This might be due to the time of the study and study population difference.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…In this study, 74% ( with CI; 70 to 78.1) of the participants had good knowledge regarding the COVID-19 outbreaks. This is higher than with the study conducted in Iran [14,17] and Saudi Arabia [18]. This might be due to the time of the study and study population difference.…”
Section: Discussioncontrasting
confidence: 60%
“…Single population proportion formula was used and the following assumptions were made: 56.5 % nurses had good knowledge regarding COVID-19 from the previous studies conducted in Iran [10], 5% marginal error (d) with 95% confidence was employed as a parameter. By assuming 10%, nonresponse rate the final sample size was 415 nurses.…”
Section: Sample Size and Sampling Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Our results are consistent with the ndings of Giao et al [9], who found that the majority of healthcare workers in Vietnam had a good level of knowledge about the COVID-19 pandemic. The result is also in line with the ndings of Nemati, Ebrahimi, and Nemati [19]. Regarding the respondents' attitude, the result showed that 85.00% of the respondents had optimistic attitudes towards COVID-19.…”
Section: Discussionsupporting
confidence: 85%